Kelompok Kecil: Strategi Efektif Bagi Pembinaan Warga Gereja - Yakub Hendrawan Perangin Angin; Hikman Sirait; Tri Astuti Yeniretnowati (Manna Rafflesia, 2022)
The small group method is very effective as a means of growing faith that leads to maturity of believers in Christ to become more like Christ. Many parachurch ministries and major churches have done it and have proven to be very effective. However, recently, many churches in urban areas have not given sufficient attention and have not considered small group discipleship as an effective strategy in cultivating church members. Even though Jesus has passed down discipleship through small groups which is very effective for Christianity to this day so that the church has a coaching pattern for every believer to grow his faith towards maturity, namely towards becoming more like Christ. For this reason, this research was carried out using library research methods from various book texts and research journals on small group discipleship. The results of this study indicate that believers and churches must make small group discipleship a strategy in faith education because it has been proven effective since the time of Jesus.